The Influence of Talent Management Practices on Employee Performance : The Mediating Role of Employee Engagement and Employee Job Satisfaction. (Case Study at PT Bank Negara Indonesia (Persero) Tbk Regional Office 02) - Fitria Khairina; Donard Games; Yulihasri (Enrichment : Journal of Management, 2022)
This study aims to examine the effect of Talent Management Practices on Employee Performance through Employee Engagement and Employee Job Satisfaction as Mediation Variables (Study on Employees of PT Bank Negara Indonesia (Persero) Tbk Regional Office 02). With research data processing is done through Smart PLS 3.3.7. The sampling technique used purposive sampling with a sample of 303 respondents. The results show that a) the application of talent management has a positive and significant effect on employee performance, b) the application of talent management has a positive and significant effect on employee engagement, c) the application of talent management has a positive and significant effect on employee job satisfaction, d) employee engagement has a positive effect. and significant on employee performance, e) employee job satisfaction has a positive and insignificant effect on employee performance, f) talent management practices have a positive and insignificant effect on employee performance through employee involvement as a mediating variable, f) talent management practices have a positive and significant effect on employee performance. employee performance employee performance through employee job satisfaction as a mediating variable.